2020
DOI: 10.4081/aiua.2019.4.211
|View full text |Cite
|
Sign up to set email alerts
|

MRI/TRUS FUSION guided biopsy as first approach in ambulatory setting: Feasibility and performance of a new fusion device

Abstract: Purpose: To evaluate the detection rate of Magnetic Resonance Imaging/Transrectal Ultrasound (MRI/TRUS) Fusion Biopsy performed in a series of patients with suspicious prostate cancer in an ambulatory setting.Materials and methods: Between March 2018 and January 2019 a series of 155 patients undergoing MRI/TRUS fusionguided biopsy were prospectively enrolled. All patients presented a suspected diagnosis for prostate cancer because of raised Prostate Specific Antigen (PSA) serum level and/or abnormal physical e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 24 publications
0
2
0
Order By: Relevance
“…Of note, the adoption of visualcognitive guidance was significantly lower in Northern Italy and in centers where more than 20 radical prostatectomies are performed monthly. Of note, the modality of lesion targeting during prostate biopsy represents a controversial and evolving issue (27)(28)(29). Beyond technical aspects, tumor multifocality is frequently involved in the discrepancies between findings from mp-MRI, prostate biopsy, and surgical specimens (29).…”
Section: Discussionmentioning
confidence: 99%
“…Of note, the adoption of visualcognitive guidance was significantly lower in Northern Italy and in centers where more than 20 radical prostatectomies are performed monthly. Of note, the modality of lesion targeting during prostate biopsy represents a controversial and evolving issue (27)(28)(29). Beyond technical aspects, tumor multifocality is frequently involved in the discrepancies between findings from mp-MRI, prostate biopsy, and surgical specimens (29).…”
Section: Discussionmentioning
confidence: 99%
“…for prostate biopsy in these anterior located lesions. Similarly, D'Agostino et al(25) found that MRI-US fusion targeted biopsy is safe and highly accurate for diagnosing csPCa especially in patients with prior negative TRUS guided prostate biopsy in their 155 patients. The primary objective of this study was to determine diagnostic efficacy and safety of transperineal mpMRI-US fusion prostate biopsy.…”
mentioning
confidence: 92%